Does Democracy Make You Happy? Multilevel Analysis of Self-rated Happiness in Indonesia - SUJARWOTO, SUJARWOTO (Universitas Muhammadiyah Yogyakarta, 2016)
The linkage between democracy and citizen happiness in developing countries is rarely examined. This study examines the link between democracy and citizen happiness in Indonesia, a new emerging democratic country in South East Asia. Data comes from the Indonesian Family Life Survey 2007 (Nindividual = 29.055; Nhousehold = 12.528; Ndistrict = 262) and the Indonesian Family Survey East 2012 (Nindividual = 5.910; Nhousehold = 2.546; Ndistrict = 55). Results from a three-level ordinary logit model show that democracy as measured by age of direct local democracy is not associated with citizen happiness. Instead of age of direct local democracy, district community social capital and spending public services give benefit for citizen happiness.The results are robust against individual and district characteristics relatedto happiness. The results highlight the importance of promoting community social capital and improving district capacity in delivering public service to improve citizen happiness in Indonesia.Keywords: democracy, happiness, three-level ordinary logit model, Indonesia